2017
DOI: 10.1038/ncomms15632
|View full text |Cite
|
Sign up to set email alerts
|

IL-17-producing γδ T cells switch migratory patterns between resting and activated states

Abstract: Interleukin 17-producing γδ T (γδT17) cells have unconventional trafficking characteristics, residing in mucocutaneous tissues but also homing into inflamed tissues via circulation. Despite being fundamental to γδT17-driven early protective immunity and exacerbation of autoimmunity and cancer, migratory cues controlling γδT17 cell positioning in barrier tissues and recruitment to inflammatory sites are still unclear. Here we show that γδT17 cells constitutively express chemokine receptors CCR6 and CCR2. While … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
113
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(120 citation statements)
references
References 55 publications
6
113
0
Order By: Relevance
“…Overall, when compared with cd1 T cells (Vc1 + and Vc4 + ), cd17 T cells (Vc4 + and Vc6 + ) showed higher expression of Cd44 and lower expression of Ptprc, which are both surface markers used for the segregation of cd1 and cd17 T cells by FACS sorting [23]. Consistent with previous reports, Vc4 + and Vc6 + cd17 T cells expressed Ccr2, Ccr6, Il7r and Il23r at a higher level and down-regulated expression of Cd27 and Sell [8,21,24,25,27,28,35]. Master transcription factors were highly expressed in the respective lineage: Rorc, Sox13, Maf and Zbtab16 in cd17 T cells and Eomes, Tbx21 and Id3 in cd1 T cells [19,27,[36][37][38][39][40][41][42][43].…”
Section: Composition Of CD T-cell Subsets In the Pln Pool Changes Dursupporting
confidence: 90%
“…Overall, when compared with cd1 T cells (Vc1 + and Vc4 + ), cd17 T cells (Vc4 + and Vc6 + ) showed higher expression of Cd44 and lower expression of Ptprc, which are both surface markers used for the segregation of cd1 and cd17 T cells by FACS sorting [23]. Consistent with previous reports, Vc4 + and Vc6 + cd17 T cells expressed Ccr2, Ccr6, Il7r and Il23r at a higher level and down-regulated expression of Cd27 and Sell [8,21,24,25,27,28,35]. Master transcription factors were highly expressed in the respective lineage: Rorc, Sox13, Maf and Zbtab16 in cd17 T cells and Eomes, Tbx21 and Id3 in cd1 T cells [19,27,[36][37][38][39][40][41][42][43].…”
Section: Composition Of CD T-cell Subsets In the Pln Pool Changes Dursupporting
confidence: 90%
“…This cell population was present in the trachea at steady state and the frequency of those cells, among the total γδ T cells, decreased over time. Although a full characterization of this subset is required, previous reports have indicated that CCR6 drives the migration of γδ17 T cells to the inflamed tissue but its expression is lost after activation to prevent the accumulation of γδ T cells in uninflamed tissues . We showed that, in addition to CCR6 + CD27 – γδ T cells, the numbers of CCR6 – CD27 – γδ T cells increased along with their CXCR3 and IL‐17A expression during infection.…”
Section: Discussionmentioning
confidence: 62%
“…95 IL-17 + cd T-cell recruitment is supported by tumor chemokine secretion, such as CCL2/MCP-1, a molecular target for anticancer therapy and ligand for CCR2, which is highly expressed on tumor-infiltrating cd T cells. 99,100 Interestingly, in other models, recruitment of IL-17 + cd T cells to the subcutaneous B16 melanoma tumors and HPVinduced skin lesions, respectively, is associated with a downregulation of CCR6 expression, 91,96 indicating that the environmental setting in which the tumor develops might influence the phenotype of the immune cells recruited. 89,90 Indeed, CCR6 and its ligand CCL20 are associated with tumor progression in models of CRC and pancreatic cancer.…”
Section: T Cells As Drivers Of Tumor Growthmentioning
confidence: 99%
“…Interestingly, the IL-17 production in cd T cells via IL-1b axis is also described in promoting tumor metastasis in a spontaneous model of breast cancer metastasis. 89,91,[96][97][98] The chemokine receptor CCR6, involved in the trafficking of IL-17 + cells to tissues at steady state, is also expressed by IL-17 + cd T cells in the tumor bed of PDA and hepatocellular carcinoma. 95 IL-17 + cd T-cell recruitment is supported by tumor chemokine secretion, such as CCL2/MCP-1, a molecular target for anticancer therapy and ligand for CCR2, which is highly expressed on tumor-infiltrating cd T cells.…”
Section: T Cells As Drivers Of Tumor Growthmentioning
confidence: 99%